A qualitative study of a non native English teacher's pedagogical system and grammar teaching / Anis Arianti Norman - Norman, Anis Arianti (2014)
Research on grammar teaching and the pedagogical system of a teacher specifically in grammar class has never come to an end. Though more new and up-to-date approaches and methodology has been introduced by scholars, some teachers still believe in certain ways to come out with classroom instruction. This study is aimed to understand the perspective on the manner of a L2 non-native English teacher in Kolej Profesional MARA Indera Mahkota, Kuantan in teaching grammar and to explore the personal pedagogical system's influence on the non-native English teacher's teaching techniques through qualitative study. The data was collected through in depth interview (pre and post) of four sections: education, entry into the profession and development as a teacher, reflection on teaching and school, and 14 hours of classroom observation (grammar class). The findings of the study is almost similar with Borg's (1998). The data indicated that the teacher's background,experience and beliefs were the factors that shaped the teacher's instruction in class.The influence of LI, the application of repetition, explanation on grammar rules,practising grammar and cooperative learning approach were the techniques used by the teacher in grammar class. The findings will benefit language teachers especially the non-native teachers in L2 setting as well as the administrative and policy makers in understanding why certain action and methods are carried out.